Personal health information management system and its application in referral management. - Maisie Wang
We developed a web-based personal health record (PHR) that can be used by patients to collect and manage their health information (e.g., medical history, past surgeries, medications, and allergies), to request self-referrals, and to store a record of their consultations. The PHR also includes a messaging system that can be structured into the workflow of referral management as well as allowing more general communications. A preliminary study was conducted with 61 patients. Thirty-two patients completed a survey in which 85% of respondents were satisfied with the usability and 94% were satisfied with the overall online referral process. The consulting physicians were satisfied with the content of subjects' personal health information and referral problem descriptions and found the information detailed enough to triage all requested referrals. Patients, physicians, and patient care coordinators reported that their communications were enhanced by the system and found the messaging component convenient to use.
Keywords: Internet; Web-based personal health record; World Wide Web; Allergies; Medical history; Medical record; Medication; Messaging system; Past surgeries; Patient care coordinator; Patient-centered care; Personal health information management system; Referral management